2019
DOI: 10.1007/978-3-030-33723-0_29
|View full text |Cite
|
Sign up to set email alerts
|

Lidar-Monocular Visual Odometry with Genetic Algorithm for Parameter Optimization

Abstract: Lidar-Monocular Visual Odometry (LIMO), a odometry estimation algorithm, combines camera and LIght Detection And Ranging sensor (LIDAR) for visual localization by tracking camera features as well as features from LIDAR measurements, and it estimates the motion using Bundle Adjustment based on robust key frames. For rejecting the outliers, LIMO uses semantic labelling and weights of the vegetation landmarks. A drawback of LIMO as well as many other odometry estimation algorithms is that it has many parameters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Binary coding with concatenated parameters is used to encode chromosomes. [19] shows one such example of GA paired with Lidar-monocular visual odometry (LIMO).…”
Section: Genetic Algorithm (Ga)mentioning
confidence: 99%
See 1 more Smart Citation
“…Binary coding with concatenated parameters is used to encode chromosomes. [19] shows one such example of GA paired with Lidar-monocular visual odometry (LIMO).…”
Section: Genetic Algorithm (Ga)mentioning
confidence: 99%
“…[8], [9], [10], and [11] are some of the closely related works. These publications' findings add to the growing body of data that using a GA to automatically modify the hyper-parameters for DRL can greatly enhance efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the closely related work includes [8], [9] and [10]. The results from these papers provide more evidence that when a GA is used to automatically tune the hyperparameters for DRL, efficiency can be largely improved.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the performance of the whole image classifier to detect a mass in a mammogram has been improved, the authors [27] do not justify the use of many constant parameters used in transferring the learning to a dataset with minimal/no ROI information. [23] and [24] have shown that automatic tuning of such parameters can greatly enhance the performance of the overall system. [23] made use of GA with Deep Reinforcement Learning (GA-DRL), and [24] used GA with Lidar-monocular visual odometry (GA-LIMO).…”
Section: Introductionmentioning
confidence: 99%
“…[23] and [24] have shown that automatic tuning of such parameters can greatly enhance the performance of the overall system. [23] made use of GA with Deep Reinforcement Learning (GA-DRL), and [24] used GA with Lidar-monocular visual odometry (GA-LIMO). Both of these works proved that when GA is used for parameter tuning, it has the potential of producing encouraging results.…”
Section: Introductionmentioning
confidence: 99%